Determination of Copper in Different Ethanolic Matrices Using a Chloropropyl Silica Gel Modified with a Nanostructured Cubic Octa(3-aminopropyl)octasilsesquioxane - Devaney Ribeiro Do Carmo; Urquisa De Oliveira Bicalho; Tayla Fernanda a Silveira; Newton Luiz Dias Filho; Leonardo Lataro Paim (Journal of Chemistry)
The chloropropyl silica gel was modified with octa(3-aminopropyl)octasilsesquioxane and characterized by Fourier transform infrared (FTIR) spectroscopy, nuclear magnetic resonance (NMR), spectroscopies, and surface and area porosity. The specific sorption capacity of metallic ions (Cu2+ and Ni2+) increases in the following solvent order: water < ethanol 42% < ethanol < ketone. The high values of the constant (K) in the order of 103 L mol−1 suggested the high adsorbent capacity of the modified silica (SGAPC) for Cu2+ and Ni2+. SGAPC was applied to a separation column and shows recoveries of around 100% of copper in samples of sugar cane spirit, vodka, ginger brandy, and ethanol fuel.